2006
DOI: 10.1002/jmv.20550
|View full text |Cite
|
Sign up to set email alerts
|

Genetic heterogeneity of the hexon gene of adenovirus type 3 over a 9-year period in Korea

Abstract: Hexon sequences were analyzed in 29 epidemiologically unrelated adenovirus type 3 (Ad3) isolates from the 7 genome types to understand the molecular basis of the genome-type diversity of Ad3 associated with childhood pneumonia in Korea during the period 1991-1999. Nine nucleotide substitutions were observed among the 29 Ad3 strains. Five of the 9 involved amino acid changes in loops 1 (Gly to Val at codon 205 and Thr to Ile at 211) and loop 2 (His to Asn at 417, Thr to Ala at 429, and Ala to Asp at 439). The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Actually, the genome type analysis showed that only two genome types among HAdV-7 were identified, but seven genome types, meanwhile, were detected among HAdV-3 in Korean children. 1,9,16,17 However, this has not been the case for HAdV-3 associated lower respiratory tract infections. Continuous circulation of HAdV-3 and the relative diversity of the HAdV-3 genome types might have produced steady state of herd immunity, 1 which resulted in persistent HAdV-3 outbreaks and showed no change of clinical severity over time.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Actually, the genome type analysis showed that only two genome types among HAdV-7 were identified, but seven genome types, meanwhile, were detected among HAdV-3 in Korean children. 1,9,16,17 However, this has not been the case for HAdV-3 associated lower respiratory tract infections. Continuous circulation of HAdV-3 and the relative diversity of the HAdV-3 genome types might have produced steady state of herd immunity, 1 which resulted in persistent HAdV-3 outbreaks and showed no change of clinical severity over time.…”
Section: Discussionmentioning
confidence: 88%
“…1,2 Among the known 53 HAdV serotypes, 3-5 particular serotypes are more commonly associated with specific diseases and multiple genetic variants exist that often have quite different geographical distributions and associated virulence. [6][7][8] During a surveillance period of 1991-2007, major respiratory viruses isolated from nasopharyngeal aspirates have been collected and comprehensive typing of respiratory HAdVs was performed in our institute.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular epidemiology or genome analysis focusing on specific serotypes such as 3, 7, or 21 have been reported previously [Kajon and Wadell, 1994;Hong et al, 2001;Kim et al, 2003;Choi et al, 2005Choi et al, , 2006a. However, a longitudinal epidemiological study of respiratory HAdVs, at the serotype level for an observational period extending 17 years has not been reported previously.…”
Section: Discussionmentioning
confidence: 95%
“…A phylogenetic separation into two genetic lineages has also been described for Korean hAdV-3 isolates. 19 The authors of this study hypothesize that these sequence variations account for an alteration of antigenic characteristics and therefore might be causative for the occurrence of hAdV-3 epidemics in the Korean population.…”
Section: Discussionmentioning
confidence: 99%